2008
DOI: 10.1038/jhh.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Low blood pressure in the very old, a consequence of imminent heart failure: the Leiden 85-plus Study

Abstract: Low blood pressure in the very old has been associated with organ dysfunction and excess mortality but the underlying mechanism has yet to be elucidated. We hypothesized that cardiac dysfunction contributes to low blood pressure in the very old. We invited a convenience sample consisting of 82 participants all aged 90 years from a population-based cohort study in the very old. Blood pressure was measured twice, and all but one underwent echocardiography to assess cardiac dimensions and functional cardiac param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
(28 reference statements)
1
20
1
3
Order By: Relevance
“…Furthermore, low blood pressure-related risk of stroke in subjects with previous functional impairment can be attributed to the fact that structural heart disease and poor cardiac functioning are associated with both low blood pressure and risk of stroke. 19 This might partially explain different associations between blood pressure measures and stroke in subjects with different levels of cognitive function, because subjects with cognitive impairment had higher prevalence of myocardial infarction and heart failure. However, subjects with physical impairment did not have more cardiovascular pathologies at 85 years of age compared with the subjects with unimpaired physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low blood pressure-related risk of stroke in subjects with previous functional impairment can be attributed to the fact that structural heart disease and poor cardiac functioning are associated with both low blood pressure and risk of stroke. 19 This might partially explain different associations between blood pressure measures and stroke in subjects with different levels of cognitive function, because subjects with cognitive impairment had higher prevalence of myocardial infarction and heart failure. However, subjects with physical impairment did not have more cardiovascular pathologies at 85 years of age compared with the subjects with unimpaired physical function.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 One possible explanation for the blood pressure decline in the oldest old might be the increasing prevalence of (subclinical) congestive heart failure. 10 Despite this dynamic correlation between blood pressure and cardiac function in relation to cognitive function in old age, previous studies have mainly focused on either the association of blood pressure or cardiac function with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that BP gradually decreases in the 3 years before death in the oldest old, suggesting that lower BP levels are a risk indicator of underlying comorbidity. 80,81 Thus, high BP may be a compensatory mechanism to maintain organ perfusion, and therefore ultimately prevents morbidity and functional decline.…”
Section: Risk Of Functional Disabilitiesmentioning
confidence: 99%